(untitled) (Research, Society and Development, 2020)
The purpose of this article is to analyze the efficiency of public spending on education in the municipalities of the state of Espírito Santo. For this matter, a descriptive methodology was used, based on a quantitative approach, through the application of the BBC model, with variable return of scale and product orientation, from the Data Envelopment Analysis (DEA). As inputs, we considered the average education expenditure per capita and GDP per capita. As a product, we used the municipal score in the Basic Education Development Index (IDEB) of Brazil, from the year 2017, considering the first years of elementary school. By creating and analyzing the ranking of efficiency that was made and used to assess the impacts of the use of budget resources in each municipality, we found that only 8.6% achieved maximum efficiency. It is concluded that, for the analyzed municipalities, the expenses with education do not necessarily imply efficiency in the area and it also suggests that an administrative review of the means of distribution of resources should be carried out in the municipalities of the state.